Karakteristik Ibu Yang Berhubungan Dengan Kejadian Balita Bawah Garis Merah Di Kecamatan Rubaru Kabupaten Sumenep - Nailiy Huzaimah; Zakiyah Yasin; Sahrul Hairi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2018)
Toddler under the red line is still a child health problem that occurs in several areas of Sumenep Regency. Rubaru Subdistrict is one of the sub-districts in Sumenep Regency which experienced an increase in the incidence of toddler under the red line in a row in 2013 to 2015. The aims of this study was to identified maternal characteristics related to the incidence of toddler under the red line in Rubaru District, Sumenep Regency. The design of this study was a descriptive study. Sampling used the total population. The number of samples is 26 mothers who have toddlers under the red line in the Rubaru Health Center area. Data collecting used questionnaire of maternal characteristics related to the incidence of toddler under the red line include age, level of education, employment, income, and knowledge of the mother. The results showed that the majority of mothers who had a BGM aged 20-30 years were 19 people (73.1%), had elementary school education were 17 people (65.4%), worked as farmers were 15 people (57.7%), low income were 18 people (69.2%), and had knowledge of toddler under the red line and good nutrition were 14 people (53.8%). The description of the characteristics of mothers who have toddler under the red line can be the basis of health workers making plans for handling them.